Pembelajaran Berbasis Proyek Untuk Anak Usia 5 – 6 Tahun di Paud Kautsar Cilegon - Laila Zulfah Nur; Ratih Kusumawardhani; Kristina Maryani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
In this study, researchers will examine the application of project-based learning for children aged 5-6 years. This research uses descriptive qualitative research methods with research data collection techniques of observation, interviews, documentation and field notes conducted in group B. Data analysis uses data reduction, data presentation and conclusions. Data analysis uses data reduction, data presentation and conclusions. Data validation is done by extending observation time, persistence in observation, triangulation, analyzing negative cases, conducting checks by members, discussions with colleagues, and checking the adequacy of references. From the results of the study, it was found that learning planning includes Prota, Prosem, and RPPH or Teaching Modules. In the implementation, there are several activities, namely core activities (children do project play activities), and recalling at the end of the activity. Learning evaluation uses child development assessment through work, narratives and checklists; supporting factors in project learning are the classroom, giving children freedom to play, and the existence of pictures of various forms of buildings according to the theme at that time in the classroom. This study aims to determine the project-based learning process at PAUD Al-Kautsar Cilegon. Children are able to think critically, express ideas and solve problems. Project-based learning for children aged 5-6 years at PAUD Al-Kautsar is going well seen from the aspects studied, namely in the aspects of point of view, finding out, asking questions, analysis and conclusions. Where children are able to develop 21st century skills, namely 4C skills: Critical thinking (critical thinking skills), creativity (creativity), communication (communication) and collaboration (cooperation).